P38 and JNK signal pathways are involved in the regulation of phlorizin against UVB‐induced skin damage. Issue 4 (6th March 2015) - Zhai, Yimiao; Dang, Yongyan; Gao, Wenke; Zhang, Ye; Xu, Peng; Gu, Jun; Ye, Xiyun
Abstract: Phlorizin is well known to inhibit sodium/glucose cotransporters in the kidney and intestine for the treatment of diabetes, obesity and stress hyperglycaemia. However, the effects of phlorizin against ultraviolet B (UVB) irradiation and its molecular mechanism are still unknown. We examined the effects of phlorizin on skin keratinocyte apoptosis, reactive oxygen species (ROS) production, pro‐inflammatory responses after UVB irradiation and the changes of some signal molecules by in vitro and in vivo assay. We observed that phlorizin pretreatments inhibited HaCaT cell apoptosis and overproduction of ROS induced by UVB. Phlorizin also decreased the expression of UVB‐induced pro‐inflammatory cytokines, such as interleukin‐1 beta (IL‐1 β ), interleukin‐6 (IL‐6) and interleukin‐8 (IL‐8) at the mRNA level. Topical application of phlorizin on UVB‐exposed skin of nude mice prevented the formation of scaly skin and erythema, inhibited the increase of epidermal thickness and reduced acute inflammation infiltration in skin. Additionally, PCR, Western blot and immunohistochemical data showed that phlorizin reversed the overexpression of cyclooxygenase‐2 (Cox‐2) induced by UVB irradiation both in vitro and in vivo . The activation of p38 and JNK mitogen‐activated protein kinases (MAPK) after UVB irradiation was also inhibited by phlorizin. These findings suggest that phlorizin is effective in protecting skin against UVB‐induced skin damage by decreasing ROS overproduction, Cox‐2 expression and the subsequent excessive inflammation reactions. It seemed that p38 and JNK MAPK signal pathways are involved in the regulation of the protective function of phlorizin.